2017
DOI: 10.1140/epjc/s10052-017-5277-8
|View full text |Cite
|
Sign up to set email alerts
|

In-medium properties of pseudoscalar $$D_s$$ D s and $$B_s$$ B s mesons

Abstract: We calculate the shift in the masses and decay constants of D s (1968) and B s (5370) mesons in hot and dense asymmetric strange hadronic matter using QCD sum rules and chiral SU(3) model. In-medium strange quark condensates ss ρ B , and gluon condensates

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 98 publications
2
22
0
Order By: Relevance
“…[53] Chhabra et al demonstrated that a moderate level of surface passivation is retained when the silicon samples are taken out of the quinhydrone-methanol solution. [57,58] For 1 Ω cm n-type silicon they achieve S of 12.6 cm s À1 (in solution) and 60.7 cm s À1 (out of solution), however for 100 Ω cm n-type silicon they achieve S of 7 cm s À1 (in solution) and 8.5 cm s À1 (out of solution).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[53] Chhabra et al demonstrated that a moderate level of surface passivation is retained when the silicon samples are taken out of the quinhydrone-methanol solution. [57,58] For 1 Ω cm n-type silicon they achieve S of 12.6 cm s À1 (in solution) and 60.7 cm s À1 (out of solution), however for 100 Ω cm n-type silicon they achieve S of 7 cm s À1 (in solution) and 8.5 cm s À1 (out of solution).…”
Section: Overviewmentioning
confidence: 99%
“…[53,55,56,59] In general, three benzyl species have been examined, hydroquinone (HQ), p-benzoquinone (BQ), and quinhydrone (QHY), where the latter is the combination of HQ and BQ. Of the three benzyl species, quinhydrone dissolved in methanol provides superior surface passivation when its concentration is 0.05 to 0.1 M. [58,59,60]…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] Gp96 binds peptides for presentation to the major histocompatibility complex class I protein (MHC-I) thereby activating a CD8 + T-cell immunogenic response. [75][76][77][78][79] Due to its ability to elicit a tumor specific response, new immunotherapies and vaccines based on Gp96 are under trial. [80,81] Rivoltini et al have shown that T-cells activated with melanoma cell line-derived Gp96-peptide can trigger cytotoxic activity in stage IV melanoma patients.…”
Section: Differential Proteins Between Good and Poor Prognosis Stage mentioning
confidence: 99%
“…The chiral SU(3) model is used vastly to investigate the in-medium properties of light mesons in nuclear and hyperonic matter [49,62,63]. To study the in-medium properties of heavy D and B mesons, this model is also generalized to SU(4) and SU(5) respectively [47,48,64,65]. In this model, the scalar and tensorial gluon condensates are extracted in terms of in-medium non-strange meson field σ, the strange scalar meson field ζ, the scalar isovector meson field δ, the vector meson field ω, the vector-isovector meson field ρ, and the dilaton field χ [46].…”
Section: Introductionmentioning
confidence: 99%